A musculoskeletal shoulder simulation of moment arms and joint reaction forces after medialization of the supraspinatus footprint in rotator cuff repair. Issue 6 (26th April 2019) - Leschinger, Tim; Birgel, Stefan; Hackl, Michael; Staat, Manfred; Müller, Lars Peter; Wegmann, Kilian
Abstract: A non-anatomical reinsertion of the supraspinatus medially to the original footprint to avoid over-tensioning of the tendon in large and retracted tears is one surgical option in rotator cuff (RC) repair. The purpose of the study was to determine the biomechanical effects on the glenohumeral joint with regard to this surgical technique. A modified musculoskeletal computational shoulder model was used to evaluate the change in moment arms and muscle forces of the RC and the co-contracting muscles and the alteration of the joint reaction forces (compressive and shear forces) after reinsertion of the supraspinatus 5 mm, 10 mm, 15 mm and 20 mm medially to the original footprint. A medialization of the supraspinatus reduces its moment arm in glenohumeral abduction. In case of a medialization of the attachment of 15 mm and 20 mm, the supraspinatus restricts glenohumeral abduction at 54° and 68°. In glenohumeral forward flexion and in lower degrees of internal rotation the moment arm of the supraspinatus increases for a medialized tendon attachment and decreases in external rotation in relation to the anatomical condition. A medialization of the supraspinatus insertion point yields in an increase in muscle force for abduction, internal and external rotation. In the present model a medially non-anatomic reinsertion reduces significantly the compressive glenohumeral joint reaction and the glenohumeral stability. Moreover, the results show that a medialization of the supraspinatus leads to a reduction of the supraspinatus moment arm especially in abduction. This leads to an increase of a compensatory supraspinatus load for stabilization the humerus in space, which may potentially cause a postoperative overload of the tendon-bone-complex.